Challenges in the Enforcement of Court Decisions in Child Custody Cases: A Case Study of the Jambi High Religious Court Decision Number 5/Pdt.G/2024/PTA.Jb - Yurnelis, Yurnelis; Tanzili, Mulyadi; Hasan, Sofyan (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
This study examines the legal implications of the non-enforcement of court decisions in child custody disputes following divorce, focusing on the Jambi High Religious Court Decision Number: 5/Pdt.G/2024/PTA.Jb. Utilizing a normative legal research method, this study analyzes relevant laws and judicial rulings. The findings indicate that although Indonesia has established a comprehensive legal framework for child protection through Law No. 35 of 2014, the execution of child custody decisions continues to face significant challenges. These challenges include inadequate communication between divorced parties, the psychological impact on children, and the lack of criminal sanctions for individuals who fail to comply with court rulings. This study recommends a holistic approach to the enforcement of custody decisions, the strengthening of legal enforcement mechanisms, and enhanced institutional coordination to ensure the effective protection of children's rights after divorce.